Current situation and countermeasures of port logistics park information construction - Zhen Liu; Ya Li; Wei Dai; Runtong Zhang (Journal of Industrial Engineering and Management (JIEM), 2013)
Purpose: Improve work efficiency of logistics park department, and drive the economy of the park and its surrounding areas. Design/methodology/approach: Analyze the information development situation and existent questions of current national logistics park, and design proper scheme to meet the demand of port logistics park. Findings: Proposed an information construction implementation plan using technology of the Internet of things which can be applied to port logistics park. Designed a scheme for the park information construction and explained the system's implementation strategy and implementation steps. Practical implications: The proposed construction program is particularly suitable for the northwest port logistics parks in China, and also has reference function to other logistics park construction. Originality/value: Group the information construction of the logistics park into four levels, three types of users, and two requirements. The scheme is innovative and comprehensive, which can ensure the development of port logistics park.
Keywords: 650; Logistics Park; Information Construction; the Internet of things; Frontier Port